Transfer of photochemistry from UV to visible: An expedient access to a bridged pyrrolidine. (9th November 2021) - Lorthioir, Olivier; Corner, Thomas; Demanze, Sylvain; Greenwood, Ryan; Proctor, Katie; Stokes, Stephen; Turner, Paul
Graphical abstract: Abstract: In this study we successfully transferred a useful photochemical reaction from the UV to the visible region of the spectrum. Use of a commercially available iridium complex facilitated triplet state intramolecular [2 + 2] photocycloaddition under irradiation with the now readily available, compact and convenient blue light sources, therefore avoiding the need for direct UV irradiation. Under these mild conditions, we enabled the efficient production of gram quantities of a medicinally relevant yet underexploited bridged pyrrolidine in a standard research lab fumehood.